Framing Development And Resistance: A Content Analysis Of Media Narratives On The Siang Upper Multipurpose Dam - Doley, Pranjit (South Asian Journal of Social Sciences and Humanities, 2025)
This study conducts a qualitative content analysis of news articles from The Hindu and The Arunachal Times, examining how media frame the proposed Siang Upper Multipurpose Project (SUMP) in Arunachal Pradesh. The analysis reveals that The Hindu predominantly frames the dam in terms of national policy, developmental progress, and strategic considerations, whereas The Arunachal Times focuses on indigenous rights, cultural and ecological concerns, and procedural issues such as the absence of Free, Prior, and Informed Consent (FPIC). The Hindu’s coverage tends to highlight institutional perspectives and national interest narratives, while The Arunachal Times amplifies grassroots opposition and local perspectives. These divergent framings illustrate the media’s dual role in both legitimizing state-led development narratives and empowering indigenous resistance. The study contributes to understanding how media narratives shape public discourse on controversial infrastructure projects, highlighting implications for environmental communication and the representation of marginalized voices.